The Impact of Funds from the Innovative Economy Operational Program on the R&D&I Performance of Poland - Elżbieta Wojnicka-Sycz; Piotr Sycz (Barometr Regionalny)
The aim of the article is to review the impact of funds from the Innovative Economy Program on the Research & Development & Innovation (R&D&I  ) performance of Poland. The paper also looks at determinants other than public support which were crucial for achievement of these results based on a systemic definition of innovation. The analysis has shown that innovation policy in the form of grants channeled through the Innovative Economy Operational Program had a clear impact on the strengthening of the R&D activity of Poland, especially those of firms. The effects of it are also visible in the form of the increased international competitiveness of Polish high technology products. However the impact on innovativeness of enterprises as a whole in Poland is not visible. It suggests that crucial would be support for turning R&D efforts into commercial innovations and widening of the number of firms receiving support from public funds, for example in the form of cheap loans to make the competition more even. Nonetheless other determinants of innovativeness like qualified personnel for R&D, the level of industrialization of the economy, the overall situation in the domestic economy as well as transparency are needed to achieve good results in terms of R&D&I.